2022
DOI: 10.1155/2022/3425225
|View full text |Cite|
|
Sign up to set email alerts
|

Discussion on the Transoral Vestibular Approach Endoscopy for TC Patients and the Significance of Serum 25-Hydroxyvitamin D Classification

Abstract: In order to discuss the transoral vestibular approach endoscopy through oral vestibular approach in TC and the efficacy of 25(OH)D classification, a total of 110 TC patients from January 2020 to June 2021 are selected. The endoscopic group and the control group are respectively established according to different surgical approaches, with 55 cases in each group. The control group received conventional TC resection, while the endoscopic group received endoscopic assisted TC resection through oral vestibular appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We analyzed data from 1,291 patients across 11 studies (Table 1) [13,16,[23][24][25][26][27][28][29][30][31], with 10 originating from Asia and one published in Europe. The predominant demographic consisted of young females undergoing TOETVA procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed data from 1,291 patients across 11 studies (Table 1) [13,16,[23][24][25][26][27][28][29][30][31], with 10 originating from Asia and one published in Europe. The predominant demographic consisted of young females undergoing TOETVA procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, recent research introduced a classification system for different mandibular jawlines, revealing varying impacts on TOETVA outcomes. Specifically, a Wang angle within the range of 80°to 110°d emonstrated a greater reduction in pain compared to a B angle exceeding 110° or a C angle below 80° [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…He et al's report on thyroidectomy anticipated that transoral vestibulectomy offers a feasible option for patients concerned about cosmetic results [8]. Previous clinical experiences have showcased the remarkable efficacy of the TOETVA in managing hyperthyroidism and benign thyroid tumors, often leading to high levels of patient satisfaction [9]. The TOETVA is performed through two incisions on the lateral lower lip, and then the tissue is dissected through the anterior neck to reach the thyroid gland [10].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%